The Case of the Javelin Thrower in the European Legal Tradition: Greek Rhetoric, Roman Casuistry, Medieval and Modern Dogmatics - Polojac, Milena (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
The case of the javelin thrower, whether real or hypothetical, has been present in the cultural and legal history of Europe for more than two and a half millennia. Thanks to ancient Greek law, and especially Justinian’s codification, this case eventually transcended its historical context and became a foundation upon which general legal theories were built. The example of a fatal outcome during a game or exercise involving javelin throwing gained particular significance within the domain of tort law (civil liability) and criminal law, serving as a model case for examining key legal questions such as causation, fault, wrongfulness, and the concept of negligence. A central issue was the legal relevance of the victim’s own fault and their contribution to the harmful event. Based on Roman casuistry, numerous legal doctrines, general definitions, conceptual distinctions, and systems of classification were developed. Later, Roman cases—including the case of the javelin thrower—were used to illustrate these abstractly formulated legal theories and concepts. However, the jurists and intellectuals who dealt with this issue and played a crucial role in the development of legal dogmatics displayed a significant degree of conservatism. For centuries, they refused to accept a simple, common-sense solution: that liability for damage could be shared or reduced when both the perpetrator and the victim were at fault. Instead, a strict "all-or-nothing" principle was consistently applied, rooted in the overwhelming authority of Roman law and the enduring influence of a deeply entrenched written legal tradition. To fully understand the processes through which legal dogmatics were formed and developed, it is essential to return to classical Roman law, which first formulated many of the fundamental legal problems that continue to occupy the attention of contemporary legal science.